EMPOWERING STUDENT ENGAGEMENT IN ENGLISH LANGUAGE LEARNING THROUGH INTERACTIVE STRATEGIES AND GRAMMAR MINI BOOKS: A SCHOOL-BASED SERVICE PROGRAM - Priyono, Ilham; Putri, Nabila Amalia (Faculty of Letters Universitas Abdurachman Saleh Situbondo, 2025)
This community service program was conducted at SMA Negeri 2 Situbondo to enhance student engagement in English language learning through the application of interactive strategies and the development of a grammar minibook. The initiative addressed key challenges such as passive student behavior, lack of confidence, and teacher-centered instruction. Using the Participatory Action Research (PAR) approach and qualitative descriptive analysis, the program involved a four-week cycle of planning, implementation, observation, and reflection. A variety of engaging activities—including digital quizzes, group discussions, educational games, and conversation simulations—were employed to foster a dynamic and participatory classroom atmosphere. Additionally, a grammar minibook titled “No More ‘Hah?’ Moments: Verbs and Modals Without Tears” was developed as a practical tool to support grammar comprehension. The results showed increased student motivation, active participation, and improved understanding of English grammar and usage. This program demonstrates that interactive teaching methods, digital media integration, and contextual learning resources can significantly improve student learning outcomes, especially in resource-limited school settings.